Protein expression pattern of tissue inhibitor of metalloproteinase-3 (TIMP3) in endometriosis and normal endometrium. (2nd December 2019) - Kotronis, Konstantinos; Zafrakas, Menelaos; Papasozomenou, Panayiota; Timologou, Anna; Miliaras, Dimosthenis; Tarlatzis, Basil C; Grimbizis, Grigorios
Abstract: Given the involvement of different extracellular matrix (ECM) metalloproteinases (MMPs) in endometriosis, the protein expression pattern of tissue inhibitor of metalloproteinase-3 (TIMP3) was analyzed in this study in endometriosis and normal endometrium. Tissue samples were collected prospectively from 64 premenopausal patients undergoing operative laparoscopy. Protein expression of TIMP3 was analyzed immunohistochemically in endometriotic lesions ( n  = 30) and normal eutopic endometrium from patients with ( n  = 35) and without ( n  = 29) endometriosis. Comparison between the three different groups of tissue samples showed that TIMP3 was differentially expressed between the three groups ( p  = .04). Pair-wise comparisons showed that TIMP3 expression was lower in endometriotic lesions as compared with normal eutopic endometrium from controls ( p  = .006); the same non-significant trend was found, in the comparison between endometriosis lesions and matched eutopic endometrium. There were no differences in TIMP3 expression in the normal eutopic endometrium between patients with and without endometriosis. In conclusion, TIMP3 seems to be involved in the pathogenesis, pathophysiology, and maintenance of endometriosis and it might be useful as a diagnostic and prognostic marker of endometriosis. Future studies should further investigate this issue, as well as the interplay between TIMPs and different extracellular MMPs in endometriosis.